Job Insecurity and Work Performance among Government's Contract Workers in Community Development Department (KEMAS)./ Noorfashihah Li - Li, Noorfashihah (2017)
The fundamental changes in the economic system thoroughly affected on how public sector being managed and operate while serving in delivering the best services to the citizen. Reorganization activities are resulting specter of losing one’s job, especially among the temporary and contract work in the public sector organization. The purpose of this study is to investigate the level of job of insecurity and work performance of the government contract worker and to ascertain the relationship between job insecurity and work performance. The questionnaire was distributed to the Community Development Department (KEMAS) which located at the Kuching, Sarawak. The respondent consists of 120 respondents, 85% female and 15% males whom age is mostly in the rage age of 21 -40 years old. Along with the data presented showing a positive weak but significant correlation between job insecurity and work performance (r=l) and at (p=. 394). Even though the result shows statistically weak positive relationship, it is merely because the level of job insecurity is relatively low, median=3.31. This shows that there are inconsistent results as compared to another study from another researcher. The data collected and analyzed from this study will allow the authorities which involving the human capital regulation to understand the level of job insecurity and work performance and eventually helps them to have the picture of overall work performance of contract worker which affected by the feeling of unsecure about the job. Theoretically, this study extending the job insecurity and the work performance study, specifically on the public sector organization’s studies. Areas for future research are also discussed in this research.